The relationship between loneliness and fear of missing out on students of the State University of Semarang - Arifiani, Zefi Nafira; Mahanani, Fatma Kusuma (Nusantara Journal of Behavioral and Social Science, 2023)
In a preliminary study conducted on 35 students at Universitas Negeri Semarang, it was found that a majority of respondents (97.1%) were female, aged 19-24 years. The study showed that all respondents felt entertained by the internet, with a significant portion using it as a diversion during sadness or boredom. Concerns about missing out on information online were prevalent, with many experiencing discomfort when unable to access the internet. The research aimed to explore the relationship between loneliness and the Fear of Missing Out (FoMO) among these students. Utilizing a sample of 400 respondents selected through cluster random sampling, loneliness and FoMO were measured using respective scales with reliabilities of 0.755 and 0.765. Spearman's Rank correlation with SPSS 21 software revealed a significant positive correlation (r=0.311, p<0.05) between loneliness and FoMO, with both variables predominantly falling in the moderate category among the students. Abstrak: Berdasarkan studi pendahuluan yang dilakukan pada 35 mahasiswa Universitas Negeri Semarang, ditemukan bahwa sebagian besar responden (97,1%) adalah perempuan berusia 19-24 tahun. Studi tersebut menunjukkan bahwa semua responden merasa terhibur oleh internet, dengan proporsi yang signifikan menggunakannya sebagai pengalihan saat sedih atau bosan. Kekhawatiran tentang ketinggalan informasi online cukup umum, dengan banyak yang merasa tidak nyaman ketika tidak bisa mengakses internet. Penelitian ini bertujuan untuk mengeksplorasi hubungan antara kesepian dan Rasa Takut Ketinggalan Informasi (Fear of Missing Out - FoMO) di antara mahasiswa tersebut. Menggunakan sampel 400 responden yang dipilih melalui sampel kluster acak, kesepian dan FoMO diukur menggunakan skala masing-masing dengan reliabilitas 0,755 dan 0,765. Korelasi Spearman's Rank dengan perangkat lunak SPSS 21 mengungkapkan korelasi positif yang signifikan (r=0,311, p<0,05) antara kesepian dan FoMO, dengan kedua variabel terutama jatuh dalam kategori sedang di antara mahasiswa.